High Throughput Identification of Antihypertensive Peptides from Fish Proteome Datasets - Yunhai Yi; Yunyun Lv; Lijun Zhang; Jian Yang; Qiong Shi (Marine Drugs, 2018)
Antihypertensive peptides (AHTPs) are a group of small peptides with the main role to block key enzymes or receptors in the angiotensin genesis pathway. A great number of AHTPs have been isolated or digested from natural food resources; however, comprehensive studies on comparisons of AHTPs in various species from the perspective of big data are rare. Here, we established a simplified local AHTP database, and performed in situ mapping for high throughput identification of AHTPs with high antihypertensive activity from high-quality whole proteome datasets of 18 fish species. In the 35 identified AHTPs with reported high activity, we observed that Gly-Leu-Pro, Leu-Pro-Gly, and Val-Ser-Val are the major components of fish proteins, and AHTP hit numbers in various species demonstrated a similar distributing pattern. Interestingly, Atlantic salmon (Salmo salar) is in possession of far more abundant AHTPs compared with other fish species. In addition, collagen subunit protein is the largest group with more matching AHTPs. Further exploration of two collagen subunits (col4a5 and col8a1) in more fish species suggested that the hit pattern of these conserved proteins among teleost is almost the same, and their phylogeny is consistent with the evolution of these fish species. In summary, our present study provides basic information for the relationship of AHTPs with fish proteins, which sheds light on rapid discovery of marine drugs or food additives from fish protein hydrolysates to alleviate hypertension.